Experimental Study on Heat Transfer and Friction Factor in Laminar Forced Convection over Flat Tube in Channel Flow. (2015) - Tahseen, Tahseen Ahmad; Rahman, M.M.; Ishak, M.
Abstract: The heat transfer and fluid flow over a flat tube in the channel with laminar forced convection is experimentally investigated. The experiments were conducted at a flat tube in the flow direction, the five air velocity between 0.2 and1.0 m/s, and Reynolds number based on the hydraulic diameter ( Re Dh ) was considered from 124.5 to 622.5. The uniform heat flux supplies are at the surface of the tube are 354.9, 1016.3 and 1935.8 W/m 2 respectively. The experimental results indicate that the average Nusselt numbers ( N u ¯ D h ) for the flat tube increased with increase of Re Dh at fixed of the heat flux supply. The N u ¯ D h increased with an increase of heat flux supply at fixed Re Dh . On the other hand, the friction factor decreased with increases of the front free stream velocity. The N u ¯ D h relationship with Re Dh in the power law, the N u ¯ D h – Re Dh correlation was found to be N u ¯ D h = C × ( Re D h ) m . The correlation achieved good predictions of the measured data with the minimum root mean square value is 99.70%.